2010
DOI: 10.1007/s00520-010-0854-5
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of health-related quality of life in children with leukemia in the second week after the diagnosis: a quantitative model

Abstract: A better knowledge of parents' views and expectations regarding their children's HRQL during the first treatments for pediatric leukemia may facilitate the communication processes in the hospital and may help to provide improved psychosocial care for the child during the first treatments for leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 30 publications
0
38
0
10
Order By: Relevance
“…13,15,46,49 Children with ALL receiving maintenance treatment reported significantly lower HRQOL as compared to children at the completion of treatment. 54 However, there was a consensus among these studies that HRQOL steadily improved as children progressed in treatment, with highest HRQOL immediately after completion of treatment.…”
Section: Time In Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…13,15,46,49 Children with ALL receiving maintenance treatment reported significantly lower HRQOL as compared to children at the completion of treatment. 54 However, there was a consensus among these studies that HRQOL steadily improved as children progressed in treatment, with highest HRQOL immediately after completion of treatment.…”
Section: Time In Treatmentmentioning
confidence: 99%
“…8 The poorest HRQOL was reported in children with AML and solid tumors, 15,48 while other studies reported finding no correlation between the type of cancer and HRQOL of children. 7,13,16,[39][40][41][42]46,49 Most of these studies measured HRQOL in a mixed sample of multiple, small diagnostic groups, thus proving difficult to interpret the effects of cancer type on the HRQOL outcome.…”
Section: Cancer Factors Considered In the Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations